1997
DOI: 10.1016/s0960-9822(06)00340-x
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog directs specialised mesoderm differentiation in the intestine and pancreas

Abstract: The generation of the pancreas and small intestine from the embryonic gut depends on intercellular signalling between the endodermal and mesodermal cells of the gut. In particular, the differentiation of intestinal mesoderm into smooth muscle has been suggested to depend on signals from adjacent endodermal cells. One candidate mediator of endodermally derived signals in the embryonic hindgut is the secreted protein Sonic hedgehog (Shh). The Shh gene is expressed throughout the embryonic gut endoderm with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
332
2
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(357 citation statements)
references
References 19 publications
22
332
2
1
Order By: Relevance
“…Removal of notochord causes ectopic Shh expression in the dorsal pancreatic anlagen and perturbs dorsal pancreas development. This early block in pancreas development was probably a consequence of altering the dorsal pancreatic mesenchyme towards a more intestinal quality (Apelqvist et al, 1997;Kim et al, 1997;Hebrok et al, 2000). As will be discussed later, dorsal pancreatic mesenchyme is an important signaling tissue that allows proliferation and morphogenesis of pancreatic progenitors after the initial budding of the anlage.…”
Section: Dorsal Pancreas Induction: Signaling From Notochord and Vascmentioning
confidence: 99%
“…Removal of notochord causes ectopic Shh expression in the dorsal pancreatic anlagen and perturbs dorsal pancreas development. This early block in pancreas development was probably a consequence of altering the dorsal pancreatic mesenchyme towards a more intestinal quality (Apelqvist et al, 1997;Kim et al, 1997;Hebrok et al, 2000). As will be discussed later, dorsal pancreatic mesenchyme is an important signaling tissue that allows proliferation and morphogenesis of pancreatic progenitors after the initial budding of the anlage.…”
Section: Dorsal Pancreas Induction: Signaling From Notochord and Vascmentioning
confidence: 99%
“…Studies in chicken and mice have demonstrated that ectopic expression of Shh during early development results in a loss of Pdx1 expression (and other pancreatic β-cell markers), and in the transformation of pancreatic mesenchyme into duodenal mesenchyme [29] [30]. In addition, continued expression of hedgehog proteins (Shh and Indian hedgehog, Ihh) after initial pancreas formation (at about E12.5 in the mouse) result in reductions in pancreatic mass, including both acinar and endocrine tissues [31].…”
Section: Pdx1 and Early Pancreas Developmentmentioning
confidence: 99%
“…During early endoderm differentiation, both Shh and Ihh are expressed strongly throughout the endodermal epithelium, with the exception of pancreatic primordia [4][5][6]. Similarly, Ptch1 is expressed in the mesenchyme adjacent to the pancreas, but expression has not been confirmed in the pancreas area of mouse embryos before embryonic day (E) 12.5 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ptch1 is expressed in the mesenchyme adjacent to the pancreas, but expression has not been confirmed in the pancreas area of mouse embryos before embryonic day (E) 12.5 [4]. Thereafter, the developing tissue starts to express several HH components [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation